2020
DOI: 10.3390/molecules26010098
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Interactions in Ionic Liquids for Natural Product Extraction

Abstract: Natural products with a variety of pharmacological effects are important sources for commercial drugs, and it is very crucial to develop effective techniques to selectively extract and isolate bioactive natural components from the plants against the background of sustainable development. Ionic liquids (ILs) are a kind of designable material with unique physicochemical properties, including good thermal stability, negligible vapor pressure, good solvation ability, etc. ILs have already been used in pharmaceutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Even though a vast number of works on the structure and properties of ionic liquids are present in the literature, experimental as well as theoretical studies are needed on this topic, especially considering those ILs that are less often used and more environmentally benign, e.g., ammonium, diazolium/triazolium, or nature-inspired ILs [ 4 , 8 , 9 ]. Two of the most widely explored groups of ILs are imidazolium and pyridinium [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though a vast number of works on the structure and properties of ionic liquids are present in the literature, experimental as well as theoretical studies are needed on this topic, especially considering those ILs that are less often used and more environmentally benign, e.g., ammonium, diazolium/triazolium, or nature-inspired ILs [ 4 , 8 , 9 ]. Two of the most widely explored groups of ILs are imidazolium and pyridinium [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Due to their low vapor pressure, they have become a sustainable alternative to the volatile organic solvents commonly used in a vast type of chemical processes, such as the extraction of valuable secondary metabolites from plants, which is well documented in the literature. [3][4][5][6] It has been claimed that the proven efficiency of ILs in the extractions of value-added compounds is enhanced due to their capacity to also solvate cellulose, which allows the goal compounds to be released in the media in larger quantities. In addition, if ultrasound radiation is used, simultaneously to ILs (ionic liquid-ultrasound assisted extraction, IL-USAE), the yield of the process increases even more.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the long alkyl chain at the imidazolium ring seems to play an important role, because other 1-alkyl-3-imidazolium bromides (where alkyl chains were C 2 H 5 , C 6 H 13 , or C 10 H 21 ) had a poorer performance. This fact was attributed by the authors to the capacity of [Dodmim][Br] to form micelles and to its appropriate viscosity; nevertheless, other authors have reported that long alkyl groups at the cation promote an increase in the viscosity of ILs, [6,19] which could avoid a proper mass transfer of the analytes.…”
Section: Introductionmentioning
confidence: 99%